1984
DOI: 10.1111/j.1365-2125.1984.tb02537.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective ring oxidation of propranolol in man.

Abstract: 1 The objective of this study was to elucidate stereoselective mechanisms of propranolol metabolism in man. Five normal subjects were given single 80 mg oral doses of deuterium-labeled pseudoracemates of propranolol, and the stereochemical composition of propranolol and its major metabolites in urine was determined by GC/MS. 2 The (-)/(+)-enantiomer ratios for unchanged propranolol, 1.50 + 0.10 (mean ± s.e. mean), and propranolol glucuronide, 1.76 + 0.10, were similar to previous findings in plasma. 3 All prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Propranolol is routinely administered to humans as the racemate. The (S) enantiomer accounts for the majority of the ␤-blocking effect, while the (R) enantiomer has a predominantly membrane-stabilizing effect (3,17,36,51). We hypothesized that the results for the racemate [(Ϯ)-propranolol] were different from the results for either of the enantiomers because of the difference in the physical properties between the racemate and the enantiomers (8,42).…”
Section: Vol 76 2010 Effects Of Pharmaceuticals On Aquatic Microorgmentioning
confidence: 62%
“…Propranolol is routinely administered to humans as the racemate. The (S) enantiomer accounts for the majority of the ␤-blocking effect, while the (R) enantiomer has a predominantly membrane-stabilizing effect (3,17,36,51). We hypothesized that the results for the racemate [(Ϯ)-propranolol] were different from the results for either of the enantiomers because of the difference in the physical properties between the racemate and the enantiomers (8,42).…”
Section: Vol 76 2010 Effects Of Pharmaceuticals On Aquatic Microorgmentioning
confidence: 62%
“…Study on properties of Propranolol pharmacological activity is historically long standing [2]. The pharmacological properties of the enantiomers of Propranolol are quite different, and the b-adrenergic blocking activity resides in the (S)-(À) enantiomer, while the (R)-(+)-enantiomer has only a membrane stabilizing effect [3][4][5][6]. Thus, separation of the enantiomers is necessary to meet the increasing demand for evaluation of the pharmacokinetic attributes of each enantiomer and to control the enantiomeric purity of pharmaceutical preparations [7].…”
Section: Introductionmentioning
confidence: 99%
“…[1] but, unfortunately, these occur in racemic forms [2]. It is well known that S-(-)-enantiomers of these drugs are about 50-500 times pharmaceutically more active than their antipodes, which act as ballast or other medication; leading to various side effects and, sometimes, toxicities [3][4][5][6][7]. It has been reported that a prolonged use of these drugs (racemic mixtures) might cause diabetes in hypertensive patients [8][9][10].…”
mentioning
confidence: 99%